The Effect of Distance Learning on Children's Moral Development - Hermawati, Wanda Alifah; Giva Salsabilla, Heidi; Rustini, Tin; Wahyuningsih, Yona (Journal of Islamic Communication and Counseling, 2022)
Moral is the foundation of a person when behaving and carrying out his role in society. In today's digital era, we can see a lot of decline in the values and morals that used to be embraced by society. Advances in the digital field do not necessarily bring moral to a more advanced level, especially during this pandemic which also exacerbates moral decline. The lack of direct interaction during learning makes students indifferent to moral values. The decline in the "price" of morals in the eyes of society can be a big threat to the harmony of a society. Therefore, many actions need to be taken to patch and repair this damaged, faded, and abandoned moral, for example, through learning in Social Sciences (IPS) subjects in collaboration with parental education at home during distance learning. In this article, the author discussed what can be done and what we can hope for to improve moral. The research applied mixed methods.